Staining susceptibility and the effect of different stain removal techniques on the optical properties of injectable composite resins - Farghal, Nancy Soliman; Awadalkreem, Fadia; Dasnadi, Shahistha Parveen; Habush, Shatha; Hatab, Nur Ali; Harhash, Asmaa (Frontiers in Oral Health, 2025)
IntroductionThe injectable composite resin technique using highly filled flowable composite for anterior restorations is relatively new. This study aims to detect the staining susceptibility and the effect of polishing and bleaching agents and their combination on the stain removal and surface gloss of the injectable composite resins compared to sculptable nanofilled composite.MethodsEighty-four disc-shaped specimens were prepared from two injectable composite resins: Beautifil Flow Plus X (BFP) and G-ænial Universal Injectable (GUI) and one sculptable nanofilled composite; Filtek™ Z350XT Universal Restorative (FUR), immersed in an instant coffee solution for 12 days. The specimens from each material were divided into four groups (n = 7) according to the stain-removal method: Group 1 (control): no stain removal treatment. Group 2: Polished with Super-Snap Buff Polisher and Direct DiaPaste for 60 s. Group 3: Bleached with Opalescence Boost 40% for one hour (3 rounds/20 min each). Group 4: bleached and polished. A Spectrophotometer recorded the color parameter initially (T0), after staining (T1) and after stain removal methods (T2) and color change (ΔE00) was calculated. Gloss (GU) was recorded initially and after stain removal methods using a glossmeter. Surface morphology was examined with Scanning Electron Microscopy. The data was analyzed using One and Two-way ANOVA and Tukey's HSD post hoc test using SPSS software at a 5% significance level.ResultsAll tested materials showed clinically unacceptable staining susceptibility after coffee immersion and stain removing methods (ΔE00 >1.8), with FUR exhibiting the highest change (26.2 ± 2.6). In-office bleaching and combined bleaching/polishing significantly reduced color change for FUR (P < 0.05), while all stain removal methods was equally effective for BPF and GUI (P > 0.05). Surface gloss remained unchanged with the highest values after staining and bleaching for all materials (52.8 ± 11.2–49.7 ± 9.4, P > 0.05) but significantly decreased after polishing alone or combined with bleaching (31.6 ± 5.7–15.4 ± 1.5, P < 0.05).ConclusionInjectable composites exhibited lower staining susceptibility than the sculptable nanofilled composite. No stain-removing method restored the color for all composites to the clinically acceptable threshold. In-office bleaching with Opalescence Boost 40% effectively maintained optimal surface gloss, while polishing alone or after bleaching is not recommended due to its negative impact on gloss.